Broad microwave absorption bandwidth achieved by exchange coupling interaction between hard and soft magnetic materials. Issue 2 (15th January 2021) - Fang, Gang; Liu, Chuyang; Yang, Yun; Peng, Kangsen; Xu, Guoyue; Zhang, Yujing
Abstract: To gain broad microwave absorption bandwidth over 2–18 GHz, hard/soft magnetic composites Ba(Zr–Ni)0.6 Fe10 · 8 O19 /Fe3 O4 have been synthesized in this work. The results show that the raising heat treatment temperature would cause more Fe3 O4 particles attach to Ba(Zr–Ni)0.6 Fe10 · 8 O19 particles, increasing the number of interfaces between Ba(Zr–Ni)0.6 Fe10 · 8 O19 and Fe3 O4 to enhance the hard/soft exchange coupling effect. Finally, the sample heat treated at 400 °C possesses the widest magnetic loss range (μ″>0.2) of 12.4 GHz, which contributes to a broad effective absorbing bandwidth of 6.68 GHz at 1.9 mm. The performance is superior than most of the state-of-the-art microwave absorbers.